Stunting Prevention: Optimizing The Family Approach With Parenting Psychoeducation - Yunia Harniati; Siti Muthia Dinni (Psikostudia : Jurnal Psikologi, 2023)
The role of parents is the most important thing in supervising the growth and development of children. The problem that is often experienced by children is stunting, to increase information to the public, namely through psychoeducation. The purpose of the activities carried out is to increase understanding and skills for stunting prevention through parenting. The intervention targets were pregnant women, adolescents, posyandu cadres, parents with toddlers and stunting, with a total of 34 participants. Sampling in this counseling using purposive sampling technique. Retrieval of data used is using observation, interviews, Focus Group Discussion (FGD). The methods used in psychoeducation are lecture, roleplay, and discussion methods. The results obtained from this psychoeducation show positive results, namely that the benefits of the psychoeducation given to participants are quite visible. The participants realized that after participating in the activity, the participants' information and understanding regarding stunting and parenting patterns increased, so that parenting psychoeducation could become one of the recommendations for the "X" Community Health Center, as well as optimizing the community for using Posyandu and increasing awareness to regularly participate in Posyandu activities.Peran orang tua salah satu faktor terpenting dalam pertumbuhan dan perkembangan anak. Masalah yang sering dialami oleh anak adalah stunting, dalam rangka meningkatkan informasi kepada masyarakat yaitu melalui psikoedukasi. Tujuan kegiatan yang di lakukan untuk meningkatkan pemahaman dan keterampilan serta pencegahan stunting melalui pola asuh. Sasaran intervensi yaitu ibu hamil, remaja, kader posyandu, orang tua yang memiliki anak balita dan stunting, dengan total keseluruhan berjumlah 34 peserta. Pengambilan sampel pada penyuluhan ini menggunakan teknik purposive sampling. Pengambilan data yang digunakan yakni menggunakan observasi, wawancara, Focus Group Discussion (FGD). Metode yang digunakan dalam psikoedukasi adalah ceramah, roleplay, dan diskusi. Berdasarkan hasil yang diperoleh dari psikoedukasi ini menunjukkan hasil yang positif, yaitu psikoedukasi yang diberikan kepada peserta cukup terlihat manfaatnya. Para peserta menyadari bahwa setelah mengikuti kegiatan, informasi dan pemahaman peserta mengenai stunting dan pola asuh anak menjadi bertambah, sehingga psikoedukasi parenting dapat menjadi salah satu rekomendasi bagi Puskesmas “ X”, serta optimalisasi masyarakat untuk pemanfaatan Posyandu dan meningkatkan kesadaran untuk rutin mengikuti kegiatan posyandu.